Medidas : uma caracterização das finalidades no ensino primário em revistas pedagógicas brasileiras (1890-1935) - Santana, Janayna Bispo (2018)
This work is the result of a research that had as objective to characterize the purposes of the measures in the primary education in Brazilian pedagogical magazines in the period from 1890 to 1928. From a mapping of researches - that somehow dealt with measures for the primary education - it was identified that the authors indicated the intuitive method from the work The First Lessons of Things, authored by Calkins (1886/1950). For this reason the option was to take the principles laid down in the Calkins manual (1886/1950) as a lens for examining copies of pedagogical journals. For the purposes, real and objective, was taken the understanding of Chervel (1990) and for appropriation was adopted Chartier (2003). In order to achieve the proposed goal, twenty-two (22) articles that explicitly refer to Calkins's intuitive method (1886/1950) were examined - whether from the author's name or the terms lessons of things and notions of things - and fifteen 15) implicit from the use of at least three of the principles set forth in Calkins's First Lessons of Things (1886/1950). As results, it can be emphasized that it was possible to characterize the purposes of the measures in three ways: First, to develop the principles of comparison and the senses of touch and vision through the relations between the size and weight of objects. In this way, the measures were part of the intuitive method proposed for primary education, in order to form the subject, not being connected only to mathematical knowledge; Second, for the conformation of the metric system, the teaching being proposed from implicit uses of principles of the intuitive method of Calkins (1886/1950) that involved: observation of objects placed before the student or the imagination, perception of similarities and differences between things, sentence formation associated with judgment, classroom model based on questioning, association of mathematical knowledge with everyday objects; Third, as part of the process of the intuitive method for the development of the metric system construction, where they were oriented from the measurement by sight without a defined unit of measurement and then verification with the metric measurement. In general, it was found that in all three purposes the principle of comparison had a primordial character, whether treated as part of the method or as part of a process of constitution of the metric system.